Acid-triggered interlayer sliding of two-dimensional copper(i)–organic frameworks: more metal sites for catalysis. Issue 18 (12th April 2021) - Zhou, Hou-Gan; Xia, Ri-Qin; Zheng, Ji; Yuan, Daqiang; Ning, Guo-Hong; Li, Dan
Abstract : The addition of TFA can trigger the interlay sliding of 2D copper(i ) organic frameworks prepared by combing the chemistry of MOFs and COFs. The variation of interlay stacking largely affected the porosity, chemical stability and catalytic activities. Abstract : The interlay sliding of two-dimensional (2D) metal–organic and covalent–organic frameworks (MOFs and COFs) affects not only the layout features of the structures, but also the functional output of the materials. However, the control of interlay stacking is the major hurdle that needs to be overcome to construct new functional layer materials. Herein, we report the preparation of a pair of isostructural 2D copper(i ) organic frameworks with an eclipsed AA stacking structure, namely JNM-3-AA, and a staggered ABC stacking topology, denoted JNM-3-ABC, by combining the chemistry of MOFs and COFs. The variation of interlayer stacking largely influences their functionality, including porosity (BET surface areas of 695.61 and 34.22 m 2 g −1 for JNM-3-AA and JNM-3-ABC, respectively), chemical stability, and catalytic activities (less than 10% or ∼86% yield using JNM-3-AA or JNM-3-ABC as catalysts for click reaction, respectively). More interestingly, the structure transformation from JNM-3-ABC to JNM-3-AA is readily achieved by simple addition of trifluoroacetic acid accompanied by the extension of porosities from BET surface areas of 34.22 to 441.22 m 2 g −1, resulting in in situ acceleration of the adoption rate (removal efficiency increases from ∼10 to 99.9%), which is rarely observed in 2D MOFs and COFs.